2008
DOI: 10.1111/j.1467-7652.2008.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered rice containing larger amounts of nicotianamine to enhance the antihypertensive effect

Abstract: SummaryNicotianamine (NA), a metal chelator ubiquitous in higher plants, serves as an antihypertensive substance in humans. To engineer a novel antihypertensive rice that contains larger amounts of NA, the barley NA synthase gene, HvNAS1 , was introduced into rice via Agrobacterium -mediated transformation. The introduced HvNAS1 was driven by pGluB-1 , which induces strong gene expression in the endosperm of rice seeds. The NA content in transgenic rice seeds was up to fourfold greater than that in non-transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…6). Usuda et al (2009) produced transgenic rice that expressed HvNAS1 under the control of an endosperm-specific promoter, OsGluB-1. NA concentration in brown seeds of this transgenic line increased threefold compared to the NT line, and Fe concentration in polished seeds also increased 1.5-fold (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…6). Usuda et al (2009) produced transgenic rice that expressed HvNAS1 under the control of an endosperm-specific promoter, OsGluB-1. NA concentration in brown seeds of this transgenic line increased threefold compared to the NT line, and Fe concentration in polished seeds also increased 1.5-fold (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the HvNAS1 gene from barley doubles concentrations of Fe and Zn in young leaves and seeds of tobacco (12). Transgenic rice seeds expressing HvNAS1 driven by the seed-specific pGluB-1 promoter also show greater amounts of NA (4-fold) and Fe (1.5-fold) (13). Likewise, overexpression of AtNAS1 in tobacco leads to higher Fe contents in the leaves (11,12).…”
mentioning
confidence: 98%
“…The supernatants were applied to an ion-exchange purification system, evaporated, and filtered for HPLC as described previously. 34) Metal concentration determination.…”
Section: Soybean Transformationmentioning
confidence: 99%
“…[31][32][33] We also reported that the NA concentration in rice seeds expressing HvNAS1 under the control of a glutelin gene promoter increased from 10 to 49.6 μg/g dry weight (DW), which is at least four times the amount in non-transgenic (NT) rice seeds. 34) We also previously reported that large amounts of NA could be produced in yeast by introducing the Arabidopsis NAS1 gene (AtNAS1). 35) Soybean (Glycine max) is an important crop, due to the large amounts of protein and lipid content in its seeds and its use as a food and energy source (American Soybean Association; http://www.soystats.…”
mentioning
confidence: 99%
See 1 more Smart Citation